Entrepeneurial Marketing for UMKM : a Literatur Review - Cicik Harini (Institute of Computer Science (IOCS), 2020)
This paper presents a literature review on entrepreneurial marketing and analyzes the factors that influence entrepreneurial marketing performance. This paper aims to contribute to the entrepreneurial marketing theory. The research method uses literature review studies derived from previous research results, journals, articles, and books. Entrepreneurial Marketing is an aspect of marketing that focuses on the need for the creation and development of a network capable of supporting companies through market penetration and e-commerce strategies.